2022
DOI: 10.1002/uog.24786
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on revised definitions of Morphological Uterus Sonographic Assessment (MUSA) features of adenomyosis: results of modified Delphi procedure

Abstract: What are the novel findings of this work?In this modified Delphi study, 13 experts on ultrasound diagnosis of adenomyosis reached consensus on revised definitions of the Morphological Uterus Sonographic Assessment (MUSA) features of adenomyosis and classified these into direct and indirect sonographic signs of adenomyosis. What are the clinical implications of this work?The revised definitions of MUSA features of adenomyosis and the distinction between direct and indirect signs should facilitate recognition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 31 publications
4
119
0
2
Order By: Relevance
“…For leiomyomas, the Steering Committee recommends reporting according to the well-established FIGO-fibroid classification ( Munro et al , 2018 ). For adenomyosis, adherence to well-defined terminology is recommended until an internationally accepted and validated reporting system is developed ( Van den Bosch et al , 2015 ; Harmsen et al , 2022 ). The scope of this work specifically excluded defining adenomyosis diagnostic criteria (imaging, histopathological or other), as the Steering Committee determined that such criteria should be defined by experts based on valid scientific evidence.…”
Section: Resultsmentioning
confidence: 99%
“…For leiomyomas, the Steering Committee recommends reporting according to the well-established FIGO-fibroid classification ( Munro et al , 2018 ). For adenomyosis, adherence to well-defined terminology is recommended until an internationally accepted and validated reporting system is developed ( Van den Bosch et al , 2015 ; Harmsen et al , 2022 ). The scope of this work specifically excluded defining adenomyosis diagnostic criteria (imaging, histopathological or other), as the Steering Committee determined that such criteria should be defined by experts based on valid scientific evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The literature has reported that readiness to diagnose and manage rare cases of UR could improve maternal-fetal outcome. Consequently, based on our experience and other authors’ opinions, high-risk patients should be promptly identified and, after counselling, referred to adequate obstetric emergency units for urgent surgical treatment [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that several 2D and 3D TVUS features are associated with adenomyosis; however the importance of each item, the minimum number of items or their combination in the diagnosis of adenomyosis has yet to be defined 1 , 31 . Indeed, there is no current consensus on the criteria for the diagnosis of adenomyosis by TVUS.…”
Section: Discussionmentioning
confidence: 99%